2023
DOI: 10.1097/eja.0000000000001904
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of explicit and implicit memories during remimazolam anaesthesia using the process dissociation procedure

Kyung Mi Kim,
Ji-Yeon Bang,
Byung-Moon Choi
et al.

Abstract: BACKGROUND Memory formation during remimazolam anaesthesia, where a bispectral index (BIS) is sometimes not maintained at less than 60 despite the maximal dose, is worthy of evaluation. OBJECTIVE Investigate the formation of explicit and implicit memories using the process dissociation procedure during remimazolam anaesthesia at a BIS of 60 to 80. DESIGN A prospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…11 Although a few studies have reported on BIS in remimazolam anesthesia, several previous findings indicate that most patients have no memory formation during general anesthesia with remimazolam at the level associated with a BIS of >60. 13,14 Kim et al 15 also demonstrated that neither explicit nor implicit memory formation occurs in patients under general anesthesia with remimzolam at BIS levels between 60 and 80. Therefore, this patient's anesthetic depth with remimazolam was most likely sufficient based on the electroencephalographic signature and her lack of complaint of any intraoperative awareness, suggesting that remimazolam could be useful as an anesthetic for patients with SPS.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although a few studies have reported on BIS in remimazolam anesthesia, several previous findings indicate that most patients have no memory formation during general anesthesia with remimazolam at the level associated with a BIS of >60. 13,14 Kim et al 15 also demonstrated that neither explicit nor implicit memory formation occurs in patients under general anesthesia with remimzolam at BIS levels between 60 and 80. Therefore, this patient's anesthetic depth with remimazolam was most likely sufficient based on the electroencephalographic signature and her lack of complaint of any intraoperative awareness, suggesting that remimazolam could be useful as an anesthetic for patients with SPS.…”
Section: Discussionmentioning
confidence: 99%